Krąg wsparcia samotnej matki zastępczej dziecka z niepełnosprawnością - Kamyk-Wawryszuk, Agnieszka (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
Between all of institutional and family’s forms of taking care about orphaned or abandoned children, in Poland and in Europe in general, foster parenting is most covets one. In foster families’ environment disabled children are present. However, only the few of potential parents are willing to take up care about child seriously disabled, demanding special rehabilitation and education. This is an experience of a two single women (from Poland), who decided to become a foster mothers and faced daily life of deep disabled children. In this paper, author tried to find an answer on following questions: how do they find themselves in the role of foster mother? What kind of support would they expect? Do they receive expected support from proper institutions? Methodology used in this paper is qualitative research, case study with narrative interview technique.
Keywords: child with disabilities; foster family; foster motherhood; single mothers